Participation of Mothers Who Work in Religious Activities Towards Child Behavior - Anti Isnaningsih; Arif Rohman (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
One of the provisions of parents to stimulate aspects of moral religious behavior in early childhood at home is by attending religious activities held in schools and places of worship. The study involved 26 children aged 4-6 years from working mothers. With a quantitative descriptive research approach the type of correlation is from mothers who have careers and participate in religious activities or not. This study looked at whether there were differences in moral religious behavior of children from both parents' backgrounds. The results showed that there were differences in the moral behavior of children's religion seen from the results of the Mann Whitney t test obtained by the results of sig. equal to 0,000 or probability value that is 0.05. The effect of caregiving is proven on the behavior of children of mothers who attend religious activities that are more controlled than children of mothers who do not attend religious activities. Children tend not to be temperament, able to resist emotions, help each other, easily forgive and get used to pray before and after doing activities. This finding proves that nurturing the role of mother in the home environment is very influential despite being busy with her work